Desorption induced formation of low-density GaN quantum dots: nanoscale correlation of structural and optical properties. (5th January 2022) - Schürmann, H; Schmidt, G; Bertram, F; Berger, C; Metzner, S; Veit, P; Dadgar, A; Strittmatter, A; Christen, J
Abstract: We report on the formation process of GaN/AlN quantum dots (QDs) which arises after the deposition of 1–2 monolayers of GaN on an AlN/sapphire template followed by a distinct growth interruption (GRI). The influence of the duration of a GRI on the structural and optical properties of the GaN layer has been systematically investigated. QDs develop from initially bulky GaN islands, which nucleate in close vicinity to bundles of threading dislocations (TDs). For prolonged GRIs, a decreasing island size is observed which is consistent with a systematic blue shift of the emission wavelength. In addition, fragmentation of the bulky GaN islands into several smaller islands occurs, strongly dependent on local strain fields caused by TDs as well as on the different facet orientation of the islands. This morphological transition during GRI eventually leads to GaN QD formation, which assemble as clusters with a density of 10 8 cm −2 . Desorption of GaN is identified as the major source for this morphological transition. The GRI time allows for tuning of the QD emission wavelength in the ultraviolet spectral range.